Performance Evaluation of a Hybrid Evaporative Cooling – Vapor Compression Air Condition - Aumpai, Natthapon; Koonsrisuk, Atit (RMUTP Research Journal Sciences and Technology, 2024)
A hybrid system combining an evaporative cooler and a traditional vapor-compression air-conditioner was investigated and evaluated its performance in this study. A 2.30m x 2.30m x 2.75m building was built at Suranaree University of Technology, Nakhon Ratchasima. A vapor-compression air-conditioner was installed in the building. Five different types of indirect evaporative coolers were built and installed in the building. They are a Maisotsenko (M) - cycle type, cross-flow with regeneration type, cross-flow without regeneration type, counter-flow with baffles type, and counter-flow without baffles type. The test results showed that the cross-flow without regeneration type provided the highest coefficient of performance (COP) and wet-bulb effectiveness compared with the other 4 types. Its maximum COP and wet bulb effectiveness were 11.68 and 0.97, respectively. This type was also easier to build because it is less complicated when compared to the others. Therefore, the cross-flow without regeneration type was chosen. It found that installing the evaporative cooler outside the building can reduce energy consumption by 30.77% compared with installing the cooler inside the building. It also found that intermittent water spraying on the cooling core is better than continuous water spraying 5 min spraying of water every 2 h can reduce the outlet air temperature of the cooler to about 8 °C.